2020
DOI: 10.1002/btpr.3073
|View full text |Cite
|
Sign up to set email alerts
|

Ectoine production in bioreactor by Halomonas elongataDSM2581: Using MWCNT and Fe‐nanoparticle

Abstract: Halomonas elongate produces ectoine to protect itselt from environmental stresses. In this research, important factors in the production of ectoine were optimized using statistical methods to achieve the best production efficiency in bioreactor. Screening important variables (ectoine, hydroxyectoine, L-aspartic acid, and glutamate) on H. elongate growth showed that ectoine and L-aspartic acid directly affect ectoine production. Two nanostructures, multiwalled carbon nanotube (MWCNT) and iron oxide nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…HPLC and MS ana­lyses revealed that the concentration of ectoine in TK1-1 mucus was 64‍ ‍mM (9.1‍ ‍g L –1 ). TK1-1 appeared to more efficiently produce ectoine without optimization than H. elongata DSM2581 ( Fatollahi et al , 2021 ).…”
Section: Resultsmentioning
confidence: 98%
“…HPLC and MS ana­lyses revealed that the concentration of ectoine in TK1-1 mucus was 64‍ ‍mM (9.1‍ ‍g L –1 ). TK1-1 appeared to more efficiently produce ectoine without optimization than H. elongata DSM2581 ( Fatollahi et al , 2021 ).…”
Section: Resultsmentioning
confidence: 98%
“…In contrast, the lack of precipitation in spring and winter and intertidal recharge introduced salinity and some heat exchange to the surface soil in order to assist Marinobacter growth, while less animal activity reduced organic matter contents and diversity in the surface soil of the restoration area, resulting in an increase in the relative abundance of Marinobacter . Similarly, to Marinobacter, the relative abundance of Halomonas was higher in the spring, especially in high-salt environments, unlike the relative abundance of Halomonas , which was lower in the winter [ 21 , 22 ]. As Gram-negative aerobic microorganisms, they exhibit higher salt acclimatization: 0.1–32.5% ( w / v ).…”
Section: Discussionmentioning
confidence: 99%
“…Ectoine is an amino acid derivative produced by bacteria living in extreme environmental conditions (high salt, high temperature, high UV radiation). As an osmoregulatory compatible solute, ectoine can increase the hydration of cell surface and stabilize the lipid layer to protect halophile cells from damage [39]. Food waste is usually characterized by high salt content.…”
Section: Genome Featuresmentioning
confidence: 99%